Formalizing a Residency Mentorship Program with a "Business of Medicine" Curriculum. (September 2020) - Sampat, Ajay; Larson, Danielle; Culler, George; Bega, Danny
Background: Mentorship is critical for achieving success in academic medicine and is also considered one of the core professional competencies for residency training. Despite its importance, there has been a decline in the mentor-mentee relationship, largely due to time constraints and lack of clear guidelines for productive discussions. We provide a mentorship curriculum with an easily adoptable workbook which may serve as a guide for programs seeking more formalized mentorship opportunities. Methods: We created a mentorship curriculum that was divided into 4 quarterly sessions, each with topics to facilitate career guidance and development, and to provide insight into the practical aspects of business of medicine. The mentorship pilot curriculum was implemented during the 2017 to 2018 academic year. Specific questions were provided to stimulate reflection and appropriate discussion between resident mentee and faculty mentor. A post-curriculum survey was distributed to evaluate the effectiveness and satisfaction of the curriculum. Results: A total of 23 residents participated in this pilot project. A majority had not had any formal teaching related to the business aspects of medicine (82%). Upon completion of the curriculum, most residents felt several topics were sufficiently covered, and a majority were satisfied with the course and relationship developed with their mentor (87%). Conclusions: Our pilot curriculum provides a model to address a knowledge gap in the practical aspects of medicine while simultaneously enhancing residency mentorship. The one-year course was generally well-received by residents and can serve as a model to other academic residency programs with similar challenges and goals.